Towards a 'peace continuum' approach to climate security: Insights from the Horn of Africa - Louise Wiuff Moe (Danish Institute for International Studies (DIIS), 2024)
Climate change is a priority area in European and broader Western initiatives for global security, with a significant focus on Africa. This paper argues that advancing the climate security agenda in Africa necessitates an approach oriented towards integrating climate adaptation and finance into a 'peace continuum', spanning prevention, peacebuilding, and development. The first section reviews gaps in advancing this agenda, notably concerning climate finance and the prioritisation of conflict-affected contexts. It asserts that addressing these gaps is essential for climate justice and for fostering partnerships in Africa amid growing global geopolitical competition. Drawing on insights from Africa's Horn, the second section discusses concrete challenges and opportunities for advancing a 'peace continuum approach' to climate security. It underscores the importance of strategic engagement and flexible, conflict-sensitive climate finance, notwithstanding challenges posed by institutional fragmentation and conflict. Recommendations are supported by examples of the UN, AU and IGAD initiatives and case studies from Somalia and Somaliland.
Keywords: 330; peace continuum; climate security; climate change; geopolitical rivalry; Africa; the Horn of Africa